Cultural memory
1 online resource (xiv, 218 pages)
Keywords: "Bringing together neuroscientists, social scientists, and humanities scholars in cross-disciplinary exploration of the topic of cultural memory, this collection moves from seminal discussions of the latest findings in neuroscience to variegated, specific case studies of social practices and artistic expressions. This volume highlights what can be gained from drawing on broad interdisciplinary contexts in pursuing scholarly projects involving cultural memory and associated topics"--